Macedonia-Alexandria : the monumental funerary complexes of the late Classical and Hellenistic age - Gorzelany, Dorota, (Archaeopress Publishing Ltd, 2019)
This text explores the influence of Macedonians and Greeks settling in Alexandria ad Aegyptum on the structural form of underground tombs, comparing in synthetic form the structural elements of the cist graves, chamber and rock-cut tombs of Macedonia with the Alexandrian hypogea, while taking into account geographical factors that conditioned them.